General symptom reporting in female fibromyalgia patients and referents: a population-based case-referent study - Johansson Saga; Wallander Mari-Ann; Björkegren Karin; Svärdsudd Kurt (BMC Public Health, 2009)
Abstract Background Fibromyalgia is characterized by widespread musculoskeletal pain and palpation tenderness. In addition to these classic symptoms, fibromyalgia patients tend to report a number of other complaints. What these other complaints are and how often they are reported as compared with related referents from the general population is not very well known. We therefore hypothesized that subjects with fibromyalgia report more of a wide range of symptoms as compared with referents of the same sex and age from the general population. Methods 138 women with diagnosed fibromyalgia in primary health care and 401 referents from the general population matched to the cases by sex, age and residential area responded to a postal questionnaire where information on marital status, education, occupational status, income level, immigrant status, smoking habits physical activity, height and weight history and the prevalence of 42 defined symptoms was sought. Results The cases had lower educational and income levels, were more often unemployed, on sick leave or on disability pension and were more often first generation immigrants than the referents. They were also heavier, shorter and more often had a history of excessive food intake and excessive weight loss. When these differences were taken into account, cases reported not only significantly more presumed fibromyalgia symptoms but also significantly more of general symptoms than the referents. The distribution of symptoms was similar in subjects with fibromyalgia and referents, indicating a generally higher symptom reporting level among the former. Conclusion Subjects with fibromyalgia had a high prevalence of reported general symptoms than referents. Some of these differences may be a consequence of the disorder while others may reflect etiological processes.